Environment, scarcity, and violence - Homer-Dixon, Thomas F. (Princeton, N.J. : Princeton University Press, 1999)
The Earth's human population is expected to pass eight billion by the year 2025, while rapid growth in the global economy will spur ever increasing demands for natural resources. The world will consequently face growing scarcities of such vital renewable resources as cropland, fresh water, and forests. Thomas Homer-Dixon argues in this sobering book that these environmental scarcities will have profound social consequences - contributing to insurrections, ethnic clashes, urban unrest, and other forms of civil violence, especially in the developing world.
Homer-Dixon is careful to point out that the effects of environmental scarcity are indirect and act in combination with other social, political, and economic stresses. He also acknowledges that human ingenuity can reduce the likelihood of conflict, particularly in countries with efficient markets, capable states, and an educated populace. But he argues that the violent consequences of scarcity should not be underestimated - especially when about half the world's population depends directly on local renewables for their day-to-day well-being.
1. Introduction -- 2. Overview -- 3. Two Centuries of Debate -- 4. Environmental Scarcity -- 5. Interactions and Social Effects -- 6. Ingenuity and Adaptation -- 7. Violence -- 8. Conclusions.
Includes index.
Keywords: Violence -- Environmental aspects -- Developing countries; Social conflict -- Developing countries; Environmental degradation -- Social aspects -- Developing countries; Renewable natural resources -- Developing countries; Scarcity -- Social aspects; Developing countries -- Environmental conditions